Injectable Disc-Derived ECM Hydrogel Functionalised with Chondroitin Sulfate for Intervertebral Disc Regeneration - Borrelli, Chiara; Buckley, Conor (My University, 2020)
Low back pain resulting from intervertebral disc (IVD) degeneration is a significant socioeconomic burden. The main effect of the degeneration process involves the alteration of the nucleus pulposus (NP) via cell-mediated enzymatic breakdown of key extracellular matrix (ECM) components. Thus, the development of injectable and biomimetic biomaterials that can instruct the regenerative cell component to produce tissue-specific ECM is pivotal for IVD repair. Chondroitin sulfate (CS) and type II collagen are the primary components of NP tissue and together create the ideal environment for cells to deposit de-novo matrix. Given their high matrix synthesis capacity potential post-expansion, nasal chondrocytes (NC) have been proposed as a potential cell source to promote NP repair. The overall goal of this study was to assess the effects of CS incorporation into disc derived self-assembled ECM hydrogels on the matrix deposition of NCs. Results showed an increased sGAG production with higher amounts of CS in the gel composition and that its presence was found to be critical for the synthesis of collagen type II. Taken together, our results demonstrate how the inclusion of CS into the composition of the material aids the preservation of a rounded cell morphology for NCs in 3D culture and enhances their ability to synthesise NP-like matrix.
PUBLISHED
Keywords: Biomaterials; Cell; Hydrogel; Repair; Self-assembly; Spine; Next Generation Medical Devices; Biomaterials